Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-04559-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Mesenchymal Stem Cell-Derived Exosomes on Experimental Autoimmune Uveitis

Abstract: We previously demonstrated that mesenchymal stem cells (MSCs) ameliorated experimental autoimmune uveoretinitis (EAU) in rats. Recently, MSC-derived exosomes (MSC-Exo) were thought to carry functions of MSCs. In this study, we tested the effect of local administration of human MSC-Exo on established EAU in the same species. Rats with EAU induced by immunization with interphotoreceptor retinol-binding protein 1177–1191 peptide were treated by periocular injections of increasing doses of MSC-Exo starting at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(218 citation statements)
references
References 43 publications
5
209
0
Order By: Relevance
“…They can ameliorate liver fibrosis, exert protective effects against acute liver injury and may enhance the anti-tumour effect against hepatocellular carcinoma [18]. MSC-exosomes have also been found to inhibit the migration of inflammatory cells, thus providing a benefit for the autoimmune disease uveitis [33]. Plenty of studies have shown their therapeutic use; however, one caveat is that the generated exosomes are not a uniform population [34,35].…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…They can ameliorate liver fibrosis, exert protective effects against acute liver injury and may enhance the anti-tumour effect against hepatocellular carcinoma [18]. MSC-exosomes have also been found to inhibit the migration of inflammatory cells, thus providing a benefit for the autoimmune disease uveitis [33]. Plenty of studies have shown their therapeutic use; however, one caveat is that the generated exosomes are not a uniform population [34,35].…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…First, the purity of the exosomes must be established based off the isolation method. Polymeric precipitation of the exosomes would require some further purification [18,32] or the ultracentrifugation of exosomes may need some additional filtering [33]. Different isolation or purification methods can also yield heterogeneous MSC-exosomes, making it difficult to compare proteomic studies between them.…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…GM-CSF, granulocyte-macrophage colony-stimulating factor. (47) or prevent the migration of pro-inflammatory M1 macrophages through interaction with chemokine ligands expressed on other tissues and cells (28,41,42,47) (Table 1). In addition, as reported by a study, SC-EVs downregulate the production of IL-23 and IL-22 and upregulate anti-inflammatory prostaglandin E2 (PGE2) by indirectly repressing the function of T helper type 17 (Th17) cell or by inducing conversion of Th17 cells into regulatory T cells (Tregs) (102).…”
Section: Scs Stem Cells; Evs Extracellular Vesicles; Sc-evs Stem Cmentioning
confidence: 99%
“…The mixed lymphocyte reaction assay indicated that these MSC-Exos performed a significant inhibitory effect on the T cell proliferation and Th1 and Th17 development [60]. However, in another experimental study focused on EAU, human umbilical cord-derived MSC-Exos (hUC-MSC-Exos) failed to suppress the proliferation of conA-stimulated T cells, but effectively inhibited inflammatory cell migration [61]. In vitro results from our group showed that hUC-MSC-Exos had only a slight suppressive effect on interphotoreceptor retinoid-binding protein (IRBP)-specific Th17 responses, while they significantly inhibited DCdriven Th17 responses through the modulation of DCderived Th17-polarizing cytokines IL-1β, IL-6, and IL-23.…”
Section: Autoimmune Uveitismentioning
confidence: 99%